2019
DOI: 10.1038/s41598-019-39457-y
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine-based Implantable Multifunctional Nanocarpet for Highly Efficient Photothermal-chemo Therapy

Abstract: We report a design and fabricate multifunctional localized platform for cancer therapy. Multiple stimuli-responsive polydopamine (PDA) was used for surface modification of electrospun doxorubicin hydrochloride (DOX) loaded polycaprolactone (PCL) fibers to make a designated platform. Photothermal properties such as photothermal performance and stability of the resulting composite mats were studied under the irradiation of the near-infrared (NIR) laser of 808 nm. With the incorporation of PDA into the fiber, a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 60 publications
2
28
0
Order By: Relevance
“…Electrospinning is a method for the facile fabrication of nanofibers under the influence of an external electric field. It allows the fabrication of continuous fibers with nano-to microscale diameters [71][72][73]. In 1887, C. V. Boys showed that fibers could be produced from a viscoelastic liquid in the presence of an external electric field [74].…”
Section: Electrospun-based Fibers As Negative Electrode Materials For Supercapacitorsmentioning
confidence: 99%
“…Electrospinning is a method for the facile fabrication of nanofibers under the influence of an external electric field. It allows the fabrication of continuous fibers with nano-to microscale diameters [71][72][73]. In 1887, C. V. Boys showed that fibers could be produced from a viscoelastic liquid in the presence of an external electric field [74].…”
Section: Electrospun-based Fibers As Negative Electrode Materials For Supercapacitorsmentioning
confidence: 99%
“…Many studies have shown that PDA with good biocompatibility and adhesion can effectively absorb NIR lasers (Maziukiewicz et al, 2019;Tiwari et al, 2019) and efficiently transform light into heat (Liu et al, 2014;Lin et al, 2018;Chen et al, 2019). Therefore, we studied the light absorption behavior of FMPBs to determine their photothermal conversion ability for PTT of tumors (Maziukiewicz et al, 2019).…”
Section: Photothermal Conversion Performancementioning
confidence: 99%
“…Many nanomaterials with an appropriate size and photothermal conversion ability are used for tumor treatment (Huo et al, 2017;Wang et al, 2019Wang et al, , 2020. During PTT, tumor cells are killed by the heat of photothermal nanoparticles after being irradiated with near-infrared (NIR) laser (Li et al, 2018;Lin et al, 2018;Tiwari et al, 2019). PTT involves the use of photothermal materials that can effectively convert light radiation into heat to cure cancer via hyperthermia (Feng et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…All in all, development of less aggressive and more effective therapies, compared to those of conventional ones, is necessary in the treatment of colorectal cancer. Since the last decade, cancer treatment by carcinoma cell ablation methods is attracting more research attention [ 9 , 10 ]. Radiofrequency ablation (RFA), microwave ablation (MWA), and laser ablation (LA) methods have been shown to be more effective in the cancer cell treatment by thermal ablation modality [ 11 ].…”
Section: Introductionmentioning
confidence: 99%